Biochar mineralization and priming effect on SOM decomposition in two European short rotation coppices. Issue 5 (12th September 2014) - Ventura, Maurizio; Alberti, Giorgio; Viger, Maud; Jenkins, Joseph R.; Girardin, Cyril; Baronti, Silvia; Zaldei, Alessandro; Taylor, Gail; Rumpel, Cornelia; Miglietta, Franco; Tonon, Giustino
Abstract As studies on biochar stability in field conditions are very scarce, the carbon sequestration potential of biochar application to agricultural soils remains uncertain. This study assessed the stability of biochar in field conditions, the effect of plant roots on biochar stability and the effect of biochar on original soil organic matter (SOM) decomposition in two (Italy and United Kingdom) short rotation coppice systems (SRCs), using continuous soil respiration monitoring and periodic isotopic (δ13CO2) measurements. When root growth was excluded, only 7% and 3% of the biochar carbon added was decomposed after 245 and 164 days in Italy and United Kingdom sites respectively. In the presence of roots, this percentage was increased to 9% and 8%, suggesting a small positive priming effect of roots on biochar decomposition. A decreased decomposition rate of original SOM was observed at both sites after biochar incorporation, suggesting a protective effect of biochar on SOM. This study supports the carbon sequestration potential of biochar and highlights the role of root activity on biochar decomposition, questioning the applicability of laboratory incubation studies to assess biochar stability.